Development of lentil germplasm for rainfed areas in Egypt - Hamdi A.; Samia Mahmoud A.; Shaaban M.; Zakia Ezatt M. (Mediterranean rainfed agriculture: Strategies for sustainability, 2004)
A new lentil (Lens culinaris Medikus) cultivar, developed in north Sinai and named Sinai 1, showed high adaptability to dry conditions and yielded 116 percent higher than the local cultivar Giza 9. This cultivar matures one month earlier and has good seed quality. The farmers in the Sinai have greatly accepted this new cultivar. In addition, there are some other lentil genotypes that are promising for rainfed areas in Egypt.
Final Seminar of the Regional Action Programme on Rainfed Agriculture (RAP-RAG), 2003/06/02-03, Zaragoza (Spain)